Les noms d’idéalités et les noms sous-spécifiés - Dejan Stosic; Nelly Flaux (Corela)
The aim of this paper is to investigate what makes some nouns belong both to the class of shell nouns (Schmid 2000, Legallois 2006) and to the class of ideality nouns (Flaux & Stosic 2015) (e.g. proposition, idea, hypothesis). Following a general overview of the main properties of these nominal classes and of their relative subdivision, we highlight their common features in order to delimit firstly the extent of their overlapping, and secondly the key factors which cause the dual membership at issue. Special attention is paid to the capacity of such nouns to allow propositional complements. With regard to the latter, we show that the range of specificational constructions in French is much broader than what is usually found in work dealing with shell nouns. This is all the more important not only to precisely delineate the extent of the intersection between shell and ideality nouns but also to refine the definition of the notion of under-specification and to better understand why some nouns pattern with propositional complements.shell nouns, ideality nouns, nominal lexicon, specification, propositional complementation